If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+8(6x-4)=2x-19
We move all terms to the left:
6x+8(6x-4)-(2x-19)=0
We multiply parentheses
6x+48x-(2x-19)-32=0
We get rid of parentheses
6x+48x-2x+19-32=0
We add all the numbers together, and all the variables
52x-13=0
We move all terms containing x to the left, all other terms to the right
52x=13
x=13/52
x=1/4
| 6x-1=3x-22 | | 36+12x=180 | | (x/4)+8=4 | | 26n=130 | | 1|4d=3 | | 2x+1+2x=101 | | x/80=5/16 | | 5m-11=—46 | | 1e-1=2 | | 3x+4(5x+2)=31x | | 2x+x=54-4x | | 3x+4(5x+2)=x | | 11t=5 | | .4(2x-12)=-28 | | 6.61+10.9d=-4.1-14.39+13.6d | | 16x+3-4-2=4-2= | | 11x-2x+3x=-48 | | 4/1x-4=1 | | -2+19u=-14+16u | | 3x-8(-3x-5)=24 | | 11x-2x+3=-48 | | -2x-16=4x+2 | | -.66(15x+3)=-3x-9 | | 12+n=-n | | k9=10 | | 2.5(x-16)=4x+12 | | -3x+7=32 | | 5(x+9)=6(x+1) | | 11x-2+3x=-48 | | -.33(15x+3)=-3x-9 | | 6/h-1=-13 | | 5(x+9)=6(×+1) |